Study the inhibitory effects of aqueous and alcoholic extracts of Melia azedarach L. on some bacterial strain. - Ali Abdulrahman .Fadhil . Fayez Owaid Neamah 2 Khairullah Farhan.3 , Lekaa Easin.4 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The current study aimed to preparation of an aqueous and alcoholic extracts of Melia azedarach L.leaves .The antimicrobial activity of these extracts was tested against four strains of bacterial isolates, two of them were Gram-positive, namely Staphyloccocus aureus NCTC6571 standard strain and Staphyloccocus aureus strain from some clinical patients. And other were Gram-negative, namely Escherichia coli ATCC25922 a standard strain and Pseuedomonas aeroginosa clinical strain isolated from some patients. Drug sensitivity test to clinical strains was also tested toward Psuedomonas aeroginosa , Staphyloccocus aureus) to Ciproflaoxacin, Cefoxitin , Strepomycin , Cefoxitin . The clinical bacterial strain Pseuedomonas aeroginosa showed resistance 100% to all antibiotics used in the experiment, while the Staphyloccocus aureus was sensitive to four antibiotics: Ampicillin, Ciproflaoxacin, Ampicillin, and Strepomycin. The current study showed the superiority of the alcoholic extract in inhibiting standard and clinical strains, including antibiotic resistance, while the aqueous extract did not show an inhibitory activity against any of the clinical bacterial, and cytotoxicity was tested using human red blood cells(RBC) , where the results showed the absence of any Cellular toxicity for all concentrations used in the experiment, so the current study recommends the possibility of using the alcoholic extract of the rosary plant as drug alternatives after conducting cytotoxicity tests and drug dose (LD50) on the mentioned extract.